2013
DOI: 10.1080/02640414.2012.762602
|View full text |Cite
|
Sign up to set email alerts
|

The mere presence of a goalkeeper affects the accuracy of penalty kicks

Abstract: The keeper-independent strategy, in which a football penalty kicker selects a target location in advance and ignores the goalkeeper's actions during the run-up, has been suggested to be the preferable strategy for taking a penalty kick. The current in-field experiment investigated the question of whether the goalkeeper can indeed be ignored. Ten intermediate-level football players were instructed to adopt a goalkeeper-independent strategy and to perform penalty kicks directed at one of two targets located in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 35 publications
2
35
2
8
Order By: Relevance
“…The central aim of the present study was to test performance consequences of directing attention towards the goalkeeper in association football penalty shootouts that have exclusively been shown in previous laboratory penalty kick studies (Navarro et al, 2013;Wilson et al, 2009;Wood & Wilson, 2010a). Most importantly, the present analyses showed that kicks that were categorised as predominantly gazing towards goalkeepers resulted in more saves and better performance by goalkeepers.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The central aim of the present study was to test performance consequences of directing attention towards the goalkeeper in association football penalty shootouts that have exclusively been shown in previous laboratory penalty kick studies (Navarro et al, 2013;Wilson et al, 2009;Wood & Wilson, 2010a). Most importantly, the present analyses showed that kicks that were categorised as predominantly gazing towards goalkeepers resulted in more saves and better performance by goalkeepers.…”
Section: Discussionmentioning
confidence: 75%
“…Pertinent to this theorising, Wood and Wilson (2010b) demonstrated that constraining penalty takers gaze to the centre of the goal resulted in shots significantly more centralised despite the participants' striving to hit distal locations. In addition, Navarro, van der Kamp, Ranvaud, and Savelsbergh (2013) showed that the mere presence of a goalkeeper impaired shot accuracy as shots were more centralised, i.e., biased towards the goalkeepereven in the absence of anxiety. If gaze is directed towards the goalkeeper prior to and at the moment of foot-ball contact, then accuracy is likely to decrease because goal-directed movements have been shown to profit from accurate and timely information derived from the foveated target (Land, 2009;van der Kamp, 2006).…”
mentioning
confidence: 97%
“…Also, according with studies previously discussed (see Introduction, section 2.4.3, particularly the response activation model), it seems that penalty kickers' perceptions might be implicitly influenced by the goalkeeper. The results of this experiment have been published (Navarro et al, 2013).…”
Section: Experiments 3: the Presence Of A Goalkeeper Influences Even Tmentioning
confidence: 74%
“…Chapter 3 provides an overview of research questions. Chapters 4-6 provide an introduction, objectives, methods, results, discussion and conclusion for the three studies completed, two published (Navarro et al, 2012(Navarro et al, , 2013 and one submitted (Navarro et al, Submitted). Finally, Chapter 7 provides a general discussion and summary of all findings, considering theoretical and practical implications.…”
Section: Structure Of the Thesismentioning
confidence: 99%
See 1 more Smart Citation